Strategic Programs to Accelerate Competency Development of Construction Workers - Siti Afrida (Pusbindiklatren Bappenas, 2022)
The quality of infrastructure highly depends on the availability of qualified, reliable, and competent and certified construction workers as stipulated in Law No. 2 of 2017. Based on the Survei Angkatan Kerja Nasional or SAKERNAS (National Labor Force Survey) conducted by Badan Pusat Statistik or BPS (Statistics Indonesia) in 2021, there are 8,293,769 million construction workers, of which less than 10% have competency certificates. This study aimed to explore the strategies for accelerating the certification of construction workers. A descriptive method with a qualitative approach was used by reviewing and observing existing data from the Ministry of Public Works and Housing, Statistics Indonesia, and Construction Services Development Agency. It was found that certification can be accelerated by establishing Certification Agency for Profession (LSP), re-branding and modernizing SIBIMA Construction services, maintaining the quality of experts through continuous professional programs (PKB), and implementing Link & Match to synchronize competency with the needs of the construction industry. It can be concluded that there has been a rise in the number of certified workers but the figures are far from the ideal target. Several factors contributed to this condition, such as lack of finance, synchronization and data harmonization, lack of synergy among the stakeholders in construction services, and lack of technology adoption and information on government policies about training and certification of construction workers.